Development of a novel block copolymer hydrogel for meniscal replacement - Fischenich, Kristine Marie, author; Haut Donahue, Tammy, advisor; Bailey, Travis, advisor; Easley, Jeremiah, committee member; Palmer, Ross, committee member; Goodrich, Laurie, committee member (Colorado State University. Libraries, 2018)
Menisci are C-shaped fibrocartilaginous tissues responsible for distributing tibial-femoral contact pressure and are crucial for maintaining healthy joints and preventing osteoarthritis. Meniscal damage can be caused by age-related degradation, obesity, overuse from athletic activities, and trauma. Due to their primarily avascular nature, once damaged there is limited healing capacity and surgical intervention is often required. Limited technologies exist to replace damaged menisci, and standard treatment is to leave asymptomatic damage alone or perform partial meniscectomies, however, these treatment options lead to increased risk of OA. Attempts at tissue engineered meniscal scaffolds, and replacements have had mixed results due to design limitations and inability to recapitulate native tissue's material properties, shape, and pressure distribution. This project strives to create an artificial meniscus from a polystyrene-polyethylene oxide diblock copolymer. It is hypothesized that this hydrogel can be tuned to have material properties similar to those of the native meniscus. Furthermore, it is hypothesized this hydrogel can be molded into a 3D meniscal construct, implanted into the joint, and have similar pressure distribution properties as the native meniscus. Thus, the aims of this project are: 1) Mechanical comparison of a polystyrene-polyethylene oxide diblock copolymer TPE hydrogel to native meniscal tissue. 2) Develop a 3D meniscal construct which can be implanted into an ovine model and assess load distribution properties including contact area, mean pressure, and max pressure in both the medial and lateral hemijoints. If the goals of this project are met, there would exist a 3D TPE hydrogel construct that mimics the mechanical and functional properties of the native human meniscus. This meniscal replacement could provide a revolutionary addition to the field of osteoarthritis and meniscal injury.
Keywords: orthopaedics; meniscus; replacement